2012
DOI: 10.1007/s12663-012-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Maxillo-Mandibular Ossifying Fibroma

Abstract: Ossifying fibroma is a benign fibro-osseous lesion which occurs at various locations in maxillofacial region. A synchronous presentation of this lesion in both, the maxilla and the mandible is a rare occurrence. The present article reports a case of ossifying fibroma in a 45-year-old woman who manifested lesions in the right maxilla and mandible. The clinico-radiologic and histopathologic modalities of diagnosing this entity are evaluated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
3
0
4
Order By: Relevance
“…Sin embargo, entre aquellos que si reportaron el tamaño, un grupo minoritario de lesiones presentaron un tamaño de 4 cm o menos (26,29,32,38,46) y en ocasiones, fueron hallazgos radiográficos (51) en radiografías bidimensionales (52) . La mayoría de las lesiones encontradas en la presente revisión superaron los 4 cm (17,19,21,22,31,34,42,45,47) , llegando hasta los 13-15 cm (45) . Esto se condice a lo encontrado en la literatura (17,19,21,22,31,34,42,45,47) , porque en general los casos se reportan cuando alcanzan un gran tamaño y generan deformación maxilofacial.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Sin embargo, entre aquellos que si reportaron el tamaño, un grupo minoritario de lesiones presentaron un tamaño de 4 cm o menos (26,29,32,38,46) y en ocasiones, fueron hallazgos radiográficos (51) en radiografías bidimensionales (52) . La mayoría de las lesiones encontradas en la presente revisión superaron los 4 cm (17,19,21,22,31,34,42,45,47) , llegando hasta los 13-15 cm (45) . Esto se condice a lo encontrado en la literatura (17,19,21,22,31,34,42,45,47) , porque en general los casos se reportan cuando alcanzan un gran tamaño y generan deformación maxilofacial.…”
Section: Discussionunclassified
“…La mayoría de las lesiones encontradas en la presente revisión superaron los 4 cm (17,19,21,22,31,34,42,45,47) , llegando hasta los 13-15 cm (45) . Esto se condice a lo encontrado en la literatura (17,19,21,22,31,34,42,45,47) , porque en general los casos se reportan cuando alcanzan un gran tamaño y generan deformación maxilofacial. La evaluación imagenológica de los FO y FCO a través de radiografías bidimensionales tiene limitaciones, tales como: distorsión, no se puede medir el vo-lumen de la lesión y no se puede establecer la relación real entre la lesión y estructuras anatómicas adyacentes (52,53) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…[19,20] Silveira et al [7] performed fixation using a reconstruction plate to completely remove the lesion in 1 patient. Tyagi et al [21] suggested that giant maxillary lesions should not be assumed to be aggressive, but should be carefully removed using thorough enucleation performed by curettage of the tumor cavity walls followed by prosthetic replacement for maxillary defects. Whether the tumor needs to be completely removed depends on the growth rate.…”
Section: Discussionmentioning
confidence: 99%